2019
DOI: 10.1063/1.5049804
|View full text |Cite
|
Sign up to set email alerts
|

Cohesive zone models to understand the interface mechanics of thin film transfer printing

Abstract: Competing fracture in the transfer of thin films from a relatively rigid host substrate to a flexible polymer substrate is studied using finite element simulations with cohesive zone models. Cohesive zone models for delamination based on traction-separation relations with a maximum stress criterion for damage initiation and mode-independent fracture energy for complete separation are explored to identify important parameters that affect transfer printing. Successful transfer of a thin film to a relatively comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…It is interesting to observe that even though the as-grown graphene is bilayer, the graphene–graphene interface did not delaminate during the dry transfer. The path of interfacial delamination could be more strongly dictated by the strength of an interface rather than the interface toughness (or adhesion energy) . Theoretical experiments using MD simulations have shown that the interlayer strength of bilayer graphene is approximately 1–4 GPa, which is orders of magnitude stronger than the experimentally determined graphene/sapphire strength of 4.1 MPa.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It is interesting to observe that even though the as-grown graphene is bilayer, the graphene–graphene interface did not delaminate during the dry transfer. The path of interfacial delamination could be more strongly dictated by the strength of an interface rather than the interface toughness (or adhesion energy) . Theoretical experiments using MD simulations have shown that the interlayer strength of bilayer graphene is approximately 1–4 GPa, which is orders of magnitude stronger than the experimentally determined graphene/sapphire strength of 4.1 MPa.…”
Section: Resultsmentioning
confidence: 98%
“…The path of interfacial delamination could be more strongly dictated by the strength of an interface rather than the interface toughness (or adhesion energy). 41 Theoretical experiments using MD simulations have shown that the interlayer strength of bilayer graphene is approximately 1−4 GPa, 42−44 which is orders of magnitude stronger than the experimentally determined graphene/sapphire strength of 4.1 MPa. The interfacial properties obtained from the measured load−displacement responses of different samples are summarized in Table 1 and Figure S14.…”
Section: Optimization Of Growth and Annealing Parametersmentioning
confidence: 98%
“…Instead of employing the cohesive zone model, Wei et al [33] proposed a numerical model using elastic interface properties to capture the stress distribution along the adhesive thickness. In order to include the non-local contributions, researchers have developed modeling approaches that explicitly account for the bridging fibers [34] or the adhesive layer [35][36][37]. Thus, to investigate the mechanisms controlling the formation of an adhesive ligament (which, in essence, corresponds to a non-local mechanism of dissipation [30]), the adhesive layer was fully modeled as a volume entity and sandwiched between cohesive elements, which mimicked a debonding at the top and bottom interfaces.…”
Section: Modeling Approachmentioning
confidence: 99%